Tinjauan Atas Penggunaan Sistem Komputerisasi Akuntansi Di Pt. Andalan Fluid System - Aspriantimi, Nahdia; Suharmiati, Suharmiati; Effendy, Marwan (Jurnal Informatika Kesatuan, 2023)
Computerized accounting system is an accounting system where the computer as information technology is useful to run applications used in processing accounting transactions and at the same time to generate financial statements in a company. With the computerized system in the company's operational activities, especially in the recording of financial statements can facilitate and help the computer user complete his activity report effectively and efficiently. The purpose of this discussion is to find out how to use computerized accounting system in PT. Mainstay Fluid system as well as in running using the system whether there are perceived obstacles, especially in the financial part.The results of the discussion showed that the computerized accounting system used by PT. Fluid System's mainstay is to use microsoft office excel in helping to make the company's financial statements. Keywords : Computerized Accounting System, Microsoft Office Excel.